Revisiting the intersection of amyloid, pathologically modified tau and iron in Alzheimer's disease from a ferroptosis perspective. (January 2020) - Derry, Paul J.; Hegde, Muralidhar L.; Jackson, George R.; Kayed, Rakez; Tour, James M.; Tsai, Ah-Lim; Kent, Thomas A.
Highlights: Iron can facilitate oxidative stress and the cell death pathway ferroptosis. The Alzheimer disease related pathological proteins, amyloid-β and tau, bind iron in various forms. In-vitro work suggests these combination entities become catalytic oxidants. Senescence, a pathology associated with aging and AD, elevates intracellular iron, and causes resistance to ferroptosis. Therapies that address multiple pathways, particularly iron-mediated, are proposed. Abstract: The complexity of Alzheimer's disease (AD) complicates the search for effective treatments. While the key roles of pathologically modified proteins has occupied a central role in hypotheses of the pathophysiology, less attention has been paid to the potential role for transition metals overload, subsequent oxidative stress, and tissue injury. The association of transition metals, the major focus heretofore iron and amyloid, the same can now be said for the likely pathogenic microtubular associated tau (MAPT). This review discusses the interplay between iron, pathologically modified tau and oxidative stress, and connects many related discoveries. Basic principles of the transition to pathological MAPT are discussed. Iron, its homeostatic mechanisms, the recently described phenomenon of ferroptosis and purported, although still controversial roles in AD are reviewed as well as considerations to overcome existing hurdles of iron-targeted therapeutic avenues that have been attempted in AD. We summarize the involvement of multiple pathological pathways at different disease stages of disease progression that supports the potential for a combinatorial treatment strategy targeting multiple factors.